Predictors of iron consumption for at least 90 days during pregnancy: Findings from National Demographic Health Survey, Pakistan (2017-2018) - Sumera Aziz Ali; Savera Aziz Ali; Shama Razzaq; Nayab Khowaja; Sarah Gutkind; Fazal Ur Raheman; Nadir Suhail (BMC, 2021)
Abstract Background Iron supplementation is considered an imperative strategy for anemia prevention and control during pregnancy in Pakistan. Although there is some evidence on the predictors of iron deficiency anemia among Pakistani women, there is a very limited understanding of factors associated with iron consumption among Pakistani pregnant women. Thus, this study aimed to investigate the predictors of iron consumption for at least ≥90 days during pregnancy in Pakistan. Methods We analyzed dataset from the nationally representative Pakistan Demographic Health Survey 2017-2018. The primary outcome of the current study was the consumption of iron supplementation for ≥90 days during the pregnancy of the last birth. Women who had last childbirth 5 years before the survey and who responded to the question of iron intake were included in the final analysis (n = 6370). We analyzed the data that accounted for complex sampling design by including clusters, strata, and sampling weights. Results Around 30% of the women reported consumed iron tablets for ≥90 days during their last pregnancy. In the multivariable logistic regression analysis, we found that factors such as women's age (≥ 25 years) (adjusted prevalence ratio (aPR) = 1.52; 95% CI: 1.42-1.62)], wealth index (rich/richest) (aPR = 1.25; [95% CI: 1.18-1.33]), primary education (aPR = 1.33; [95% CI: 1.24-1.43), secondary education (aPR = 1.34; [95% CI: 1.26-1.43), higher education (aPR = 2.13; [95% CI: 1.97-2.30), women's say in choosing husband (aPR = 1.68; [95% CI: 1.57-1.80]), ≥ five antenatal care visits (aPR =2.65; [95% CI (2.43-2.89]), history of the last Caesarian-section (aPR = 1.29; [95% CI: 1.23-1.36]) were significantly associated with iron consumption for ≥90 days. Conclusion These findings demonstrate complex predictors of iron consumption during pregnancy in Pakistan. There is a need to increase the number of ANC visits and the government should take necessary steps to improve access to iron supplements by targeting disadvantaged and vulnerable women who are younger, less educated, poor, and living in rural areas.